2020
DOI: 10.3390/ijerph17020431
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trends in Urban Atmospheric Polycyclic Aromatic Hydrocarbons and Nitropolycyclic Aromatic Hydrocarbons: China, Russia, and Korea from 1999 to 2014

Abstract: Total suspended particulate matter (TSP) was collected during the summer and winter in five cities in China (Shenyang, Beijing, and Shanghai), Russia (Vladivostok), and Korea (Busan) from 1997 to 2014. Nine polycyclic aromatic hydrocarbons (PAHs) with four to six rings, including pyrene (Pyr) and benzo[a]pyrene (BaP), were determined using high-performance liquid chromatography with fluorescence detection. Two nitropolycyclic aromatic hydrocarbons (NPAHs), 1-nitropyrene (1-NP) and 6-nitrobenzo[a]pyrene (6-NBaP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 18 publications
1
16
1
Order By: Relevance
“…PAHs concentration in PS and MM were lower than that measured in a long-term monitoring study in the United States (Liu et al, 2017) and in an 1-year study in India (Kumar et al, 2020). The period of sampling could highly influence the concentration of PAHs (Hayakawa et al, 2020), since one of the most important anthropogenic source of PAHs is the primary emissions from residential heating, especially biomass burning, during the cold season (Tomaz et al, 2016). Moreover, the high concentration of pollutants in the cold season could also be due to the variation of the thickness of the planetary boundary layer (PBL), the volume of air where the atmospheric pollutants are dispersed.…”
Section: Polycyclic Aromatic Hydrocarbon (Pahs)mentioning
confidence: 63%
“…PAHs concentration in PS and MM were lower than that measured in a long-term monitoring study in the United States (Liu et al, 2017) and in an 1-year study in India (Kumar et al, 2020). The period of sampling could highly influence the concentration of PAHs (Hayakawa et al, 2020), since one of the most important anthropogenic source of PAHs is the primary emissions from residential heating, especially biomass burning, during the cold season (Tomaz et al, 2016). Moreover, the high concentration of pollutants in the cold season could also be due to the variation of the thickness of the planetary boundary layer (PBL), the volume of air where the atmospheric pollutants are dispersed.…”
Section: Polycyclic Aromatic Hydrocarbon (Pahs)mentioning
confidence: 63%
“…Nevertheles, there was a significant increasing trend during both seasons in 2010 and summer in 2017. Based on our previous research, according to the Asia Pacific Economic Cooperation (APEC) meeting in 2012, many infrastructure construction projects were under construction in Russia from 2007 to 2012, which may have led to an increase in the concentration of PAHs [ 25 ]. In addition, the Russia–China naval activities in the Sea of Japan and the Sea of Okhotsk in September 2017 [ 73 ] may have led to an increase in ∑PAHs, and the impact of these emergencies on PAHs cannot be ignored.…”
Section: Resultsmentioning
confidence: 99%
“…The residential heating period lasts appromixmately six months every year. Our previous study in Vladivostok demonstrated that coal combustion was the major source of ambient PAHs and NPAHs in winter [ 25 , 26 ]. This study also showed that human activities and local government energy policies directly influence the concentrations and compositions of PAHs and NPAHs.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, China accounted for 24% of global energy consumption of which coal and oil accounted for 58% and 18.9%, respectively (bp p.l.c., 2019;NBSC, 2019). As a result, the concentration of atmospheric PAHs in China is much higher than that of some Asian, European and American countries (Sanderson et al, 2004;Delhomme and Millet, 2012;Shen et al, 2013;Tang et al, 2017;Zhang et al, 2019a;Hayakawa et al, 2020), although strict air pollution control measures instituted by China have effectively improved air quality in recent years (Zheng et al, 2018;Zhang et al, 2019c).…”
Section: Introductionmentioning
confidence: 99%